“Welcome to the LGBTQIA+ side of TikTok”: Genders and sexualities in algorithmic mediations (Simbiótica. Revista Eletrônica, 2023)
The main screen of the Chinese application TikTok, used to create and share short videos, is called “for you”, which is where the algorithm directs videos, according to what it assumes to be interesting to the person watching. TikTok's conventional content is composed of challenges, choreographies and celebrity impersonations, in addition to these, there is alternative content that, when directed by the algorithm, produces what people in the application call "sides". One of these sides of TikTok is LGBTQIA+. In this anthropological essay I discuss how gender and sexuality are experienced in the LGBTQIA+ side of TikTok. At the end of the text, I consider that, regardless of labels, on this side of TikTok, magnets and other things (in the Ingold’s sense) are inhabited as a place where various happenings intertwine.